Intestinal Perforation and Prolapse Due to Jejunostomy: Case Report (Global Journal of Medical Research, 2020)
Objective: Report the case of a patient who presented complications due to incorrect handling of the tube during jejunostomy, in order to demonstrate data that corroborate the importance of proper management. Case Detail: A 60-year-old male patient with jejunostomy was admitted to the emergency department presenting prolapse. He underwent urgent laparotomy, which revealed jejunal loop perforations and Foley tube cuff hyperinflation with food content. Was performed reduction of the jejunal prolapse, removal of the tube after perforation and cuff emptying, as well as two-plane enterorraphy at the perforation sites and Stamm-Senn gastrostomy were performed. Final considerations: It can be observed that complications are relatively infrequent, but they cannot be disregarded, and the attending physician should emphasize the importance of proper management of jejunostomies by the caregivers in order to avoid such complications.
Keywords: jejunostomy; intestinal perforation; prolapsed